Enhanced cell-surface display of a heterologous protein using SED1 anchoring system in SED1-disrupted Saccharomyces cerevisiae strain - Bamba, Takahiro; Inokuma, Kentaro; Hasunuma, Tomohisa; Kondo, Akihiko (Journal of bioscience and bioengineering, 2018)
Yeast displaying enzymes on the cell surface are used for developing whole-cell biocatalysts. High enzyme activity on the cell surface is required in certain applications such as direct ethanol production from lignocellulosic materials. However, the cell surface enzyme activity is limited by several factors, one of which is the protein amount of the yeast cell wall. In this study, we attempted to improve the incorporation capacity of a displayed heterologous enzyme by disrupting a native cell-wall protein. β-Glucosidase (BGL1) from Aspergillus aculeatus was fused with Saccharomyces cerevisiae Sed1 and displayed on the cell surface of S. cerevisiae BY4741 strain and its SED1 disruptant. Sed1 is one of the most abundant stationary phase yeast cell wall protein. A time course analysis revealed that BGL1 activity of the control strain reached saturation after 48 h of cultivation. In contrast, the BGL1 activity of the SED1 disruptant increased until 72 h of cultivation and was 22% higher than that of the control strain. We also performed relative quantification of cell wall proteins of these strains by nanoscale ultra pressure liquid chromatography electrospray ionization quadrupole time-of-flight tandem mass spectrometry (nano-UPLC-MSE). The amount of the cell wall-associated BGL1 per unit dry cell-weight of the SED1 disruptant was 19% higher than that of the control strain. These results suggested that the incorporation capacity of the cell wall for BGL1 was increased by disruption of SED1. Disruption of SED1 would be a promising approach for improving display efficiency of heterologous protein fused with Sed1.